Evaluation of the effect of Low-Level LASER Therapy on Anxiety Level in 6 to 12-year-old Children undergoing Dental Treatment under Local Anesthesia: A Randomized Controlled Trial - Siddhi Jitendra Bora; Dimple Padawe; Vilas Takate; Vandana Tripathi; Kishor Dighe; Medha Tanna (Ann Publisher, 2026)
Background: Dental anxiety is a common challenge in pediatric dentistry and can negatively affect cooperation and treatment outcomes, particularly during procedures involving local anesthesia. Safe, non-invasive interventions that reduce anxiety are therefore of clinical interest. The present study aimed to evaluate the effect of low-level laser therapy (LLLT) delivered as laser acupuncture on anxiety levels in children undergoing dental treatment under local anesthesia. Materials and Methods: This randomized controlled in vivo study included 80 children aged 6–12 years who required dental treatment under local anesthesia. Participants were randomly allocated to an LLLT group (n = 40) or a placebo control group (n = 40). Laser acupuncture was applied at auricular and hand Shenmen points 15 minutes before anesthesia in the intervention group, while the control group received a sham procedure. Anxiety was assessed using physiological parameters (pulse rate and oxygen saturation) and a psychological measure (Facial Image Scale, FIS). Statistical analysis was performed with a significance level set at p < 0.05. Results: Baseline pulse rate and oxygen saturation were comparable between groups (p > 0.05). Post-intervention, the LLLT group showed a significantly greater reduction in pulse rate (−4.13 ± 5.66 bpm) compared with the control group (−0.23 ± 3.24 bpm; p = 0.0003). Oxygen saturation increased in the LLLT group (+0.40 ± 1.13%) but decreased slightly in controls (−0.20 ± 1.36%; p = 0.035). Mean FIS scores were significantly lower in the LLLT group (1.85 ± 0.95) than in the control group (2.25 ± 1.01; p = 0.03). Conclusion: Pre-procedural low-level laser acupuncture significantly reduced both physiological and subjective indicators of dental anxiety in children undergoing treatment under local anesthesia, supporting its use as a practical adjunct in pediatric dental care.